FAMILY BUSINESS SUCCESSION PLANNING: UNLEASHING THE KEY FACTORS OF BUSINESS PERFORMANCE - Wee Yu Ghee,; Mohamed Dahlan Ibrahim,; Hasliza Abdul-Halim, (Asian Academy of Management Journal, 2015)
Family business studies are becoming more pervasive in Malaysia, and several studies have focused on factors that shape family-owned business performance levels. Succession planning issues, and specifically the succession issues and experiences of second or third generation family business owners (2GO/ 3GO), have not yet been explored at length. This study aims to revisit various factors that shape family firm performance by examining succession issues and transition experiences encountered by successors. Data were drawn from self-administered surveys completed by 55 2GOs and 3GOs. Descriptive, correlation and regression analyses were conducted to interpret our findings. The findings show that management styles, relationships between family members, values and beliefs and successor training significantly influence family business performance levels. The relationship between antecedents and business performance is found to be partly mediated by succession issues and fully mediated by sucession experience. Both theoretical and practical implications and avenues for future research are discussed.